Implementation of partnership program policy on micro, small and medium enterprises in accelerating poverty alleviation in Bekasi City - Prihandono, Prihandono; Raharjo, Paiman; Sukmana, Pandji; Rachmatsyah, T. Herry (Edelweiss Applied Science and Technology, 2024)
The purpose of this research is to ascertain how the policies of the Partnership programme have affected micro, small, and medium-sized businesses in Bekasi city with an eye towards rapidly reducing poverty. The author employs a descriptive technique based on qualitative approaches for her research. Researchers in this study gathered information from a maximum of nine sources. The outcomes demonstrated that the policy of the Partnership programme, when applied to micro, small, and medium-sized businesses in accelerating poverty alleviation in Bekasi city has not been running optimally and still needs to be improved. Data collection for large companies that have carried out partnership programs, facilitating capital assistance, socialization and extension that can be expanded, providing exhibition space or promotion as an effort made and facilitated by the Bekasi small and Medium Business Cooperative Office in the MSME partnership program.